2.4n+1.2-0.12=48

Simple and best practice solution for 2.4n+1.2-0.12=48 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2.4n+1.2-0.12=48 equation:


Simplifying
2.4n + 1.2 + -0.12 = 48

Reorder the terms:
1.2 + -0.12 + 2.4n = 48

Combine like terms: 1.2 + -0.12 = 1.08
1.08 + 2.4n = 48

Solving
1.08 + 2.4n = 48

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-1.08' to each side of the equation.
1.08 + -1.08 + 2.4n = 48 + -1.08

Combine like terms: 1.08 + -1.08 = 0.00
0.00 + 2.4n = 48 + -1.08
2.4n = 48 + -1.08

Combine like terms: 48 + -1.08 = 46.92
2.4n = 46.92

Divide each side by '2.4'.
n = 19.55

Simplifying
n = 19.55

See similar equations:

| x^2+28=11x | | -15x^2-44x+32=0 | | 6x^2-26= | | 12x^2+21x+-6=0 | | 6x^2+7x+-2=0 | | 4x^2-6x+9= | | -5x-7=13 | | 6x^2+7+-2=0 | | 3(2n+7)=3 | | 7x-4y=23 | | 6(u+6)-3=10 | | 4r-11=-12+5r | | m^2-4m=5 | | 13x+39=9 | | p+36+(p-37)+2*p=491 | | x^4-5x^2+40= | | p+36+2(p-37)+p=491 | | p+36+2(p-37)+p=699 | | 8m-3=-3+6m | | -10p-2(3p-6)=4(5p-6)-10p | | 4x^2+2x-25=0 | | 2(4s-7)=-15-5s | | an=6n+14 | | .9x=8+2.25x | | 1-1=b | | 9x=12x-9 | | 1+b=2 | | 55+3x=8x | | 9y^4-12y^3+36y^8=0 | | 17-3a=-6a-1 | | 4-9y=-23 | | x^3+7x=8x^2 |

Equations solver categories